Cleaning up after human activity in Antarctica: legal obligations and remediation realities - Indiah Hodgson-Johnston; Andrew Jackson; Julia Jabour; Anthony Press (2017)
National Antarctic Programmes do not have a strict legal obligation to remediate the Antarctic environment following human activity. The Protocol on Environmental Protection to the Antarctic Treaty (the “Madrid Protocol”) obliges parties to conduct environmental impact assessments to prevent adverse impacts on the polar environment and to “clean up” pollution from waste disposal sites. The obligations stemming from the Madrid Protocol are not clearly defined, and give potential scope for parties to neglect past sites of human activity on the continent. This scope is narrowed by the work of the Committee for Environmental Protection in implementing clear practical clean-up guidelines for National Antarctic Programmes based on scientific-based recommendations from the Antarctic Treaty Parties. Despite better modern practice, Parties are still faced with damage from past activities. Some of these sites are deemed to be “beyond help.” This article proposes that rather than abandoning waste disposal sites because of widely acknowledged difficulties, that National Antarctic Programmes prioritize research into restorative methodologies and techniques, while increasing cooperation with other parties to overcome the enormous logistical and economic costs of cleaning up pollution in Antarctica.